Experimental investigations of the Hydro-Spinna turbine performance. (December 2016) - Rosli, R.; Norman, R.; Atlar, M.
Abstract: A unique tidal turbine, "Hydro-Spinna", is introduced. The Hydro-Spinna consists of three cardioidal blades spiralling around a common horizontal shaft. A 500 mm diameter model was manufactured and its performance investigated in the towing tank facility of Newcastle University. The main objective of these experiments was to investigate the hydrodynamic efficiency of Hydro-Spinna with a view to improve the design by collecting data for use in numerical optimization. Considering its flexible operating characteristics the model turbine was tested at different immersion depths and in the half-submerged condition. The power coefficient of the turbine reached a value of almost 0.3 at a tip speed ratio of 2.2 in the fully submerged condition. The turbine had a higher power coefficient in shallow immersion and half submerged condition. The drag coefficient on the whole system decreased with increasing TSR contrary to conventional turbines. The turbine was observed to start rotating at low flow velocities, down to 0.15 m/s. In the study, although the turbine presents a relatively low power coefficient compared to that of competitive turbines, its unique adaptability of immersion depth, including the partially submerged condition, low starting flow velocity and rotational speed offer an interesting prospect for a range of applications. Highlights: A novel tidal current turbine called the "Hydro-Spinna" was introduced. Main features and geometry of the turbine were defined. A 500 mm model was manufactured and tested in the towing tank facility of Newcastle University. The power performance were explored experimentally at varying depths of submergences including at half submerged condition. Overall results were discussed and main conclusions were drawn in relation to the hydrodynamic performance of the Hydro-Spinna.